6FDA‐containing polyimide‐ionene + ionic liquid gas separation membranes. Issue 18 (23rd August 2020) - Dennis, Grayson P.; O'Harra, Kathryn E.; Kammakakam, Irshad; Jones, Tristin A.; Mittenthal, Max S.; Flowers, Brian S.; Tuan, Yi; Jackson, Enrique M.; Bara, Jason E.
Abstract: Polyimides (PI) synthesized from 4, 4′‐(hexafluoroisopropylidene)diphthalic anhydride (6FDA) with various diamines have been frequently studied as gas separation membranes. The use of 6FDA in polyimides creates a bent structure than can increase fractional free volume (FFV) and gas permeability. Here, we demonstrate that 6FDA is also a useful building block for PI‐ionene materials, which contain cations directly within the polymer backbone. These new 6FDA‐containing PI‐ionenes were combined with several different imidazolium ionic liquids (ILs) to form thin membranes. The thermal properties of all the derivatives were investigated to determine the relationship between regiochemistry and degradation as well as the intermolecular forces that are present within these structures. The gas separation properties of these 6FDA‐containing PI‐ionene + IL materials were investigated, showing modest CO2 permeabilities similar to other polyimide‐ionenes and CO2 /CH4 and CO2 /N2 permselectivities that were relatively higher than other polyimide‐ionenes. Abstract : The synthesis of polyimide membranes for energy‐efficient gas separations typically relies on the reaction of a dianhydride with a diamine. Although effective, this conventional approach limits the number of potential structures and compositions available to study. However, 6FDA‐containing polyimide‐ionenes and composites with ionic liquids open vast new opportunities in the design of polymer gas‐separation membranes for applications such as the removal of CO2 from industrial processes.